2015
DOI: 10.1590/1983-21252015v28n309rc
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência Agronômica Do Consórcio Alface-Rúcula Fertilizado Com Flor-De-Seda

Abstract: Resumo -O presente trabalho teve como objetivo avaliar o desempenho agronômico do consórcio de alface e rúcula fertilizado com diferentes quantidades de biomassa de flor-de-seda incorporadas ao solo. O experimento foi conduzido no período de setembro a novembro de 2011, na área de pesquisa da Fazenda Experimental Rafael Fernandes da Universidade Federal Rural do Semi-Árido, Mossoró-RN. O delineamento experimental utilizado foi em blocos ao acaso com cinco tratamentos e quatro repetições. Os tratamentos consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 8 publications
2
26
1
13
Order By: Relevance
“…These data were contrary to those reported by Almeida et al (2015) who observed higher productivity of lettuce and arugula when green manure was applied. The greatest number of roses of control shows that the intercropping with green manures was not favorable for the development of plants, as may have been competition between rosebushes and legumes.…”
Section: Resultscontrasting
confidence: 99%
“…These data were contrary to those reported by Almeida et al (2015) who observed higher productivity of lettuce and arugula when green manure was applied. The greatest number of roses of control shows that the intercropping with green manures was not favorable for the development of plants, as may have been competition between rosebushes and legumes.…”
Section: Resultscontrasting
confidence: 99%
“…On the other hand, the decreasing responses of these characteristics after the optimal values was due to the Law of the Maximum, where the excess of a nutrient in the soil may cause toxic effect and/or diminish the effectiveness of others, resulting in reduced values of these variables (Almeida et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The narrow C:N ratio situated in the range between 20 to 30:1 of the roostertree in the edaphoclimatic conditions of the semiarid region of Pernambuco allowed a rapid mineralization and release of nutrients (GÓES et al, 2011;ALMEIDA et al, 2015). Snyder et al (2009) found that shoot mass, total and commercial productivity of carrots enhanced with increases in N availability, but they highlighted that the mineralization of other nutrients from plant biomass are essential to increase productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation of this legume to adverse conditions such as drought stress, heat or salt stress, its high production of dry biomass, about 40 t ha -1 , vigorous regrowth after cutting and C/N ratio less than 30:1, have justified the increased interest of agronomic researchers on roostertree use as green manure (SOUTO et al, 2008;ANDRADE FILHO, 2012). Research results have demonstrated the potential use of this specie as green manure in the radish crop , carrot (SILVA et al, 2013), coriander , arugula (SOUZA et al, 2016) and lettuce-arugula intercropping (ALMEIDA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%